PELATIHAN KETERAMPILAN PENDUKUNG PENELITIAN DAN PENULISAN ARTIKEL - Siti Fatimah Zahra (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2022)
Research is one of the tri dharma tasks carried out by a lecturer and student. Lack of knowledge of lecturers and students in basic research skills will hinder competence in creating quality research in the development of science and have an impact on the lack of scientific publications. Therefore, seeing that there is still little research being held, this PKM activity aims to improve the ability of partners in terms of skills in conducting research and writing articles through training that discusses 5 main topics, namely Access to International Journals, Paraphrasing, Referencing Manager Software with Mendeley, Turnitin, and Microsoft Word Advance. The implementation of this PKM activity is carried out in 4 stages: 1. Identification and determination of target participants, identification of needs, implementation of training and evaluation of activities. This training was attended by 168 participants from 4 partner campuses, namely Buana Perjuangan University, Trisakti School of Management, Mpu Tantular University, and Semarang State University. Many participants were enthusiastic about the material presented, as seen by the many questions and answers with participants during the training discussion session. It is hoped that this training can improve the abilities of the participants and the number of researches.